Stress at the helm: the prevalence and key risk factors of occupational stress among port workers in the port terminal industry - Yaakub, Norwahida; Abdul Razak, Nur Fazhilah; Baharuddin, Mohd Rafee; Mohd Noor, Mohd Azhar (Universiti Putra Malaysia Press, 2024)
Introduction: In Malaysia, there is a lack of data on the prevalence of occupational stress among port terminal workers. The study's goal was to find out how common and risky occupational stress was for those who worked at the port terminal. Methods: Designing a cross sectional structure was done at the port terminal. In order to determine the prevalence of occupational stress, the Job Content Questionnaire (JCQ) assesses four factors: social support, job uncertainty, psychological job demands, and decision latitude. Results: A remarkable 68.8 percent of workers reported experiencing some form of work-related stress, indicating a high level of occupational stress in the workplace. The age factor has shown a significant association with work-related stress among the sociodemographic factors (p-value =0.038). Social support (p-value =0.01), task (p-value =0.00), exposure (p-value =0.02), skilled work (p-value = 0.04), and organizational culture (p-value =0.00), and company culture were all found to be significantly linked to the risk of occupational stress. Conclusion: This study sheds light on the alarming prevalence of occupational stress among Malaysian port terminal employees. The identified factors, including age, social support, task-related aspects, exposure levels, specialized work involvement, and organizational culture, play crucial roles in defining the risk of occupational stress in this context. These results not only contribute to the current understanding of the issue, but also provide important insights for future research and interventions aimed at addressing and mitigating occupational stress among port workers. © 2024 Universiti Putra Malaysia Press. All rights reserved.